SIKAP KERJA SAMA SISWA PADA PEMBELAJARAN SOSIAL MELALUI MODEL THINK PAIR SHARE (TPS) - Fina Lailatul khusna; imaniar purbasari; Mohammad Kanzunnudin (Jurnal Prakarsa Paedagogia, 2020)
Study aims to describe and analyze how much the improvement in student collaborative abilities use Think Pair Share (TPS) model in my hero theme social learning 2019/2020. student look passive in learning and low levels of student cooperation that can be seen in the absence of activities to help and motivate each outher among group members, in addition it looks student who lack appreciation among individuals in the group. This class action research was counducted in fourth grade students with 18 research subjects. This class action research two cycles, each cycle consisting of two meetings. Each cycle consists of the stages of planning, implementation, observation, and reflection. The results showed an increase in learning. This can be seen from the fulfillment of the follow indicators of success, Cooperative attitude of students in learning action cycle I obtained an average percentage success of 61% the category (good) and an increase in the second cycle of 84% category (good).